Pertanggungjawaban Pidana terhadap Pelaku Tindak Pidana yang Diancam dengan Pasal 112 Ayat (1) Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika - Ikhwanul Dawam Sulawijaya; Papang Sapari; Gindo L Tobing (Syntax Corporation, 2023)
A more crucial problem which is also the main topic of discussion in this research is the provisions of other articles whose impact may be to close the opportunity for medical rehabilitation for narcotics addicts and abusers, namely the provisions in Article 112 paragraph (1) of Law no. 35 of 2009. Example of the case of Central Jakarta District Court Decision Number 51/Pid.Sus/2022/PN Jkt.Pst, related to Article 112 paragraph (1). The research method used is the normative juridical method, namely research that prioritizes library data, namely research on secondary data. This secondary data can be in the form of primary, secondary or tertiary legal materials. This research includes research regarding the positive legal provisions in force in Indonesia relating to criminal liability for perpetrators of criminal acts which are threatened with Article 112 paragraph (1) of Law Number 35 of 2009 concerning Narcotics. Based on the research results, the author concludes that the rationale for the establishment of Article 112 paragraph (1) of Law Number 35 of 2009 concerning Narcotics, is not a denial of the principle of legality) in principle it is to realize justice for the defendant and the community. And if there is a conflict between justice and law enforcement, then the sense of justice must take priority. Meanwhile, the problems that arise from Article 112 paragraph (1) of Law Number 35 of 2009 include: a) It can criminalize drug addicts and abusers who should be given the right to rehabilitation. What is meant here is the vulnerability of this article being used to criminalize people who are not actually involved in criminal acts but whose cases are fabricated as if they were carrying or controlling narcotics.